Determination of maximum acceptable weight of schoolbag carriage in one shoulder - Soares, Helena (2022)
Pain and discomfort are prevalent symptoms among children and adolescents in school age. Carrying heavily loaded schoolbags or carrying it improperly, such as in a single shoulder, has been related to this symptomatology. In view of this, it is important to better understand the students' perceptions about what they consider to be a safe weight to carry.